2003
DOI: 10.1079/phn2003491
|View full text |Cite
|
Sign up to set email alerts
|

Empowered women, social networks and the contribution of qualitative research: broadening our understanding of underlying causes for food and nutrition insecurity

Abstract: Objective: To investigate underlying causes for food and nutrition insecurity in black South African households and to gain understanding of the factors contributing to better nutrition security, with emphasis on household organisation, gender and intrahousehold dynamics and social networks. Design, setting and subjects: Within a larger cross-sectional survey that investigated the impact of urbanisation on the health of black South Africans, 166 people, mostly women, were interviewed on household food security… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 7 publications
1
45
0
Order By: Relevance
“…The subjects Table 1 shows that the sizes of the households on farms tended to be smaller (possibly because children were sent away to schools or families with food security) 4,24 . The majority of rural households had very low to low incomes while subjects from urban households reported moderate to high incomes (groups 4 and 5, 58.1 and 75.6%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subjects Table 1 shows that the sizes of the households on farms tended to be smaller (possibly because children were sent away to schools or families with food security) 4,24 . The majority of rural households had very low to low incomes while subjects from urban households reported moderate to high incomes (groups 4 and 5, 58.1 and 75.6%).…”
Section: Resultsmentioning
confidence: 99%
“…Other questionnaires. A number of validated structured and open-ended questionnaires were designed, validated and used to obtain information on household food security 24 , knowledge and attitudes towards obesity, reproductive behaviour, parity, breast-feeding 25 and colorectal cancer risk 26 in sub-samples.…”
mentioning
confidence: 99%
“…Wirth et al [2007] found that income was the single greatest predictor of hunger and food insecurity, followed by migratory status. On the other hand, strong social support systems are protective against food insecurity [Lemke et al, 2003;Hadley and Sellen, 2006] and hunger [Martin et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…A relatively unexplored aspect is the contribution of interpersonal relationships in this context. Some researchers have suggested that interpersonal and community-level social relationships, particularly the resources they provide, would help vulnerable people in handling this adverse condition (33)(34)(35)(36) .…”
mentioning
confidence: 99%